PENGARUH MEDIA PEMBELAJARAN MAPAJA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SD MUHAMMADIYAH MERANJAT - Berliana Putri Ramadhan; Treny Hera; Iswahyuni Wulandari (LPPM Universitas Cipta Mandiri, 2024)
This research was conducted because learning is still carried out conventionally and uses minimallearning media so that student learning outcomes have not reached the criteria for completeness. Theresearch aims to determine whether there is a significant influence on the learning outcomes of classII students at SD Muhammadiyah Meranjat who are taught using Mapaja learning media. Thisresearch uses an experimental method, namely True Experimental Design using the Pretest-PosttestControl Group Design test form. The test consists of 10 multiple choice questions. The sample in thisstudy consisted of two classes, namely the experimental class with 16 students and the control classwith 17 students. The results of the hypothesis test obtained a value of tcount of 2.455 while ttablewas 1.697 so that Ho was rejected and Ha was accepted, so it can be concluded that the Mapajalearning media has a significant effect on the mathematics learning outcomes of reading timestampsin class II of SD Muhammadiyah Meranjat.